1978
DOI: 10.1128/iai.22.1.22-28.1978
|View full text |Cite
|
Sign up to set email alerts
|

Radiolabeling of Treponema pallidum (Nichols virulent strain) in vitro with precursors for protein and RNA biosynthesis

Abstract: We observed uptake of [U-'4C]serine, U-'4C-labeled amino acid hydrolysates, and [2-'4C]uracil by virulent Treponema pallidum in vitro for at least 96 h. No uptake of [2-'4C]thymine, [1-'4C]pyruvate, [U-14C]pyruvate, and [2-'4C]uridine was detected. Treponemal protein and RNA biosynthetic activity was identified by erythromycin inhibition of amino acid and uracil uptake. Radioactivity due to uptake of radiolabeled amino acids by residual testicular cells in the cultures remained at background levels regardless … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
1
0

Year Published

1979
1979
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
3
1
0
Order By: Relevance
“…Analysis of acid-hydrolyzed nucleic acid showed that glucose was utilized for the synthesis of both ribose and deoxyribose, which implicates the action of several enzymes for the utilization of pentoses in the biosynthesis of nucleotides (28). These findings were consistent with the ability of T. pallidum to incorporate nitrogenous bases into nucleic acid (32,33,36). Also noteworthy were the investigations by Baseman and coworkers (8,32) which showed that nucleosides were also utilized for nucleic acid biosynthesis.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Analysis of acid-hydrolyzed nucleic acid showed that glucose was utilized for the synthesis of both ribose and deoxyribose, which implicates the action of several enzymes for the utilization of pentoses in the biosynthesis of nucleotides (28). These findings were consistent with the ability of T. pallidum to incorporate nitrogenous bases into nucleic acid (32,33,36). Also noteworthy were the investigations by Baseman and coworkers (8,32) which showed that nucleosides were also utilized for nucleic acid biosynthesis.…”
Section: Discussionsupporting
confidence: 74%
“…Studies on the anabolic capacities of T. pallidum have described the incorporation of amino acids into proteins (5, 6) and nucleosides and nitrogenous bases into nucleic acids (8,32,36). The treponeme has also been observed to sequester free fatty acids from the environment (37).…”
Section: Discussionmentioning
confidence: 99%
“…pallidum was shown by Sandok and Jenkin in 1978 [46]. This study confirmed the absorption of serine, amino acid hydrolysates and uracil by T. pallidum in vitro by radiolabeling [46].…”
Section: Media Tested In the Attempts To Culture T Pallidumsupporting
confidence: 81%
“…Conversely, Noguchi strains T. refringens [11] Nichols avirulent T. refringens [11] in co-culture assays with mammalian cells, the positive impact of amino acids on the survival of T. pallidum was shown by Sandok and Jenkin in 1978 [46]. This study confirmed the absorption of serine, amino acid hydrolysates and uracil by T. pallidum in vitro by radiolabeling [46].…”
Section: Use Of Amino Acids As Nutrientssupporting
confidence: 67%